Growth of flexible and porous surface layers of vertical graphene sheets for accommodating huge volume change of silicon in lithium-ion battery anodes. (September 2020) - Han, M.; Lin, Z.; Ji, X.; Mu, Y.; Li, J.; Yu, J.
Abstract: Silicon (Si) has been a focus material as lithium-ion battery (LIB) anode due to its ultrahigh theoretical specific capacity (4200 mA h/g). However, huge volume change ( 400%) during cycling and low electrical conductivity have adversely affect its cycling life and rate performance, delaying its footstep as commercial anode of LIBs. Herein, vertical graphene sheets (VGSs) are grown on Si particles by thermal chemical vapor deposition, which forms a flexible and porous surface layer. The VGSs encapsulated Si particles (VGSs@Si) have a low volume deformation (12.9% in thickness after 100 cycles) and a high lithium ion diffusion coefficient (1.5 × 10 −12 –4.4 × 10 −9 cm 2 /s), arising from good flexibility, high porosity, and excellent electrical conductivity of VGSs. As LIB anode, the VGSs@Si nanocomposite delivers a high reversible capacity of 2696.1 mAh/g, a long cycling life (500 cycles with capacity retention of 80.1% at 2 A/g), and an outstanding rate capability (457.9 mA h/g at 20 A/g). Remarkably, the full cell with prelithiated VGSs@Si as anode and commercial LiCoO2 as cathode shows a high gravimetric energy density of 514.6 W h/kg and volumetric energy density of 1126.5 W h/L. Graphical abstract: Image 1 Highlights: VGSs@Si that vertical graphene sheets grow on Si is obtained by thermal CVD. The VGSs can ease the huge volume change of Si due to flexibility and porosity. The VGSs@Si has ultrahigh DLi+ due to superior electrical conductivity of VGSs. The VGSs@Si shows excellent lithium ion storage performances in half and full cells.